The natural product bergenin ameliorates lipopolysaccharide-induced acute lung injury by inhibiting NF-kappaB activition. (22nd March 2017) - Yang, Shengqian; Yu, Ziru; Wang, Lin; Yuan, Tianyi; Wang, Xue; Zhang, Xue; Wang, Jinhua; Lv, Yang; Du, Guanhua
Abstract: Ethnopharmacological relevance: Bergenin, an active constituent of the plants of the genus Bergenia, was reported to have anti-inflammatory effects in the treatment of chronic bronchitis and chronic gastritis clinically. However, its therapeutic effect on lipopolysaccharide (LPS)-induced acute lung injury (ALI) and its potential mechanisms of actions were still unknown. Aim of this study: To evaluate the effect of bergenin on murine model of acute lung injury induced by LPS and also to explore its potential mechanisms. Materials and methods: Half an hour and 12 h after an intranasal inhalation of LPS, male BALB/c mice were treated with bergenin (50, 100 and 200 mg/kg) or dexamethasone (DEX, 5 mg/kg) by gavage. Twenty-four hours after LPS exposure, the lung wet/dry ratio, histological changes, myeloperoxidase (MPO) in lung tissues, inflammatory cells (in BALF) and cytokines (in BALF and serum) were detected. Meanwhile, the protein expression of MyD88 and the phosphorylation of NF-κB p65 in lung tissue were analyzed using immunoblot analysis. Moreover, the nuclear translocation and the phosphorylation of NF-κB p65 in Raw264.7 cells were also analyzed. The viability of Raw264.7 cells was determined by MTT assay. Results: Results showed that bergenin significantly decreased pulmonary edema, improved histological changes and reduced MPO activity in lung tissues. Moreover, bergenin obviously decreased inflammatory cells, IL-1β and IL-6 production in BALF, as well as IL-1β, TNF-α and IL-6 production in serum of LPS-induced ALI mice. Furthermore, bergenin markedly inhibited LPS-induced NF-κB p65 phosphorylation, as well as the expression of MyD88 but not the expression of NF-κB p65 in lung tissues. Additionally, bergenin also significantly inhibited the nuclear translocation and the phosphorylation of NF-κB p65 stimulated by LPS in Raw264.7 cells. Conclusions: These findings suggested that bergenin had a therapeutic effect on LPS-induced ALI by inhibiting NF-κB activition. Graphical abstract: